2010
DOI: 10.1159/000322373
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Health and Memory Predictors of Mild Cognitive Disorders and Cognitive Decline in Ageing: The Personality and Total Health (PATH) through Life Study

Abstract: Aims: To investigate self-reports of memory and health as predictors of transition to mild cognitive impairment (MCI) or any mild cognitive disorder (any MCD) in a community-based study. Method: 2,082 individuals, aged 60–64 years, were assessed at 2 time points 4 years apart for MCI using either the International Consensus Criteria, the Clinical Dementia Rating scale (CDR, 0.5), or a suite of criteria sets for mild cognitive disorders (any MCD) and global cognitive change. Logistic and multiple regression was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
39
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 77 publications
6
39
0
Order By: Relevance
“…Subjective ratings of health have been shown to be associated with impairment in functional and cognitive status [20] and brief self-reports, which can be easily obtained, have shown potential for predicting cognitive decline [21] . While the literature has traditionally focused on measures of objective cognitive impairment, there is increasing focus on the significance and measurement of subjective cognitive impairment, especially subjective memory impairment or subjective memory complaints.…”
Section: Introductionmentioning
confidence: 99%
“…Subjective ratings of health have been shown to be associated with impairment in functional and cognitive status [20] and brief self-reports, which can be easily obtained, have shown potential for predicting cognitive decline [21] . While the literature has traditionally focused on measures of objective cognitive impairment, there is increasing focus on the significance and measurement of subjective cognitive impairment, especially subjective memory impairment or subjective memory complaints.…”
Section: Introductionmentioning
confidence: 99%
“…SMD has been found to be associated with APOE ε4 genotype, 7 with an almost twofold increased risk of incident dementia, 3,8,9 a fourfold increased risk of incident MCI, 10 and with prospective cognitive decline. 11,12 Associations between SMD and objective neuropsychological measures have been found to be weak, 13 however, and SMD has low predictive value for dementia.…”
mentioning
confidence: 99%
“…SargentCox and colleagues found that those reporting that SMD interfered with their day-to-day life were at a threefold increased risk of developing MCI over 4 years. 10 Differences between reports and self-initiated complaints may therefore reflect important distinctions in the nature or the timing of underlying processes, although some overlap is likely. For example, in cross-sectional analyses Anstey and colleagues 20 found that individuals with stable MCI, who were more likely to report having memory problems which interfered with daily life, were also more likely to have consulted a doctor about memory concerns.…”
mentioning
confidence: 99%
“…Unlike AD-related biomarkers, data regarding the psychological determinants of subtle cognitive deterioration in healthy elders are still scarce [11,12]. Among them, personality traits have been drawing growing interest since they are associated with MCI status and may modulate independently dementia risk in MCI [13,14,15].…”
Section: Introductionmentioning
confidence: 99%